Asuhan Keperawatan pada Klien Ny. D dan Ny. S yang Mengalami Ketidakefektifan Pemberian ASI dengan Post SC atas Indikasi Preeklampsia - Alvina, Alvina; Umar, Ahmad Farid; Herlina, Herlina (Jurnal Persada Husada Indonesia, 2024)
Post Partum is the period after labor and birth of the baby, placenta and membranes that are needed to restore the uterine organs to the way they were before pregnancy and takes approximately 6 weeks. Sectio Caesarea is a delivery procedure to remove the baby through an incision in the abdomen and uterus. Preeclampsia or what is usually called pregnancy with hypertension, is not like hypertension in general but is closely related to high morbidity and mortality rates for both the fetus and mother. Breast milk is the best food for babies who do not have food intake to replace breast milk. The subjects in the case study used 2 clients who experienced ineffective breastfeeding in the Ponek Room at Bekasi City Regional Hospital. The design in this research uses a qualitative approach with descriptive study analysis. The results of research conducted on the client Mrs. D & Mrs. S is that in this study the same 5 diagnoses were found, namely impaired comfort and pain, activity intolerance, ineffectiveness of breastfeeding, risk of ineffective peripheral perfusion and risk of infection. The diagnostic intervention that is the focus is the ineffectiveness of breastfeeding. Implementation carried out on 2 clients, namely assessing the condition of the client's breasts and nipples, carrying out and teaching breast care and oxytocin massage, encouraging mothers to breastfeed their babies as often as possible, involving husbands and families about breast care, providing education about breast milk. The evaluation of the 2 clients has been completed.